Controlled Hypotension for Functional Endoscopic Sinus Surgery: A Comparative study between Dexmedetomidine versus Esmolol (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Background: Functional endoscopic sinus surgery (FESS) requires effective control of bleeding forbetter visibility of the operating field and reduced risk of injury to the optic nerve or the internal carotidartery. Controlled hypotension is a technique used to limit intraoperative blood loss to provide the bestpossible field for surgery.Objectives: Our study is undertaken to evaluate the efficacy of dexmedetomidine as a hypotensive agentin comparison to esmolol in Functional Endoscopic Sinus Surgery (FESS).Method: Sixty (60) patients 20 – 50 years of age, ASA I/II scheduled for FESS were equally randomlyassigned to two equal groups of 30 patients each. Patients of group D received dexmedetomidine 1μg/kgover 10 min before induction of anesthesia followed by 0.4 – 0.8 μg/kg/hr infusion during maintenanceand group E received esmolol loading dose 1mg/kg was infused over one min followed by 0.4 – 0.8 mg/kg/hr infusion during maintenance to maintain mean arterial blood pressure (MAP) between (55 – 65mmHg). The surgical field was assessed using Average Category Scale and average blood loss wascalculated. Hemodynamic variables (MAP, HR); intraoperative fentanyl consumption and total recoveryfrom anesthesia (Aldrete’s score e”9) were recorded. Sedation score was determined at 10, 20, 30, 40 & 60min after tracheal extubation and time to first analgesic demand was also recorded.Results: In both group D and group E reached the desired MAP (55 – 65 mmHg) with no intergroupdifference in MAP or HR. Mean intraoperative fentanyl consumption was significantly lower in group Dthan group E. Recovery time to achieved Aldrete’s score e”9 were significantly lower in group E comparedwith group D. The sedation score were significantly lower in group E compared with group D at 10minutes, 20 minutes and 30 minutes postoperatively. Time to first analgesic demand was significantlylonger in group D.Conclusion: The result of this study showed that both dexmedetomidine and esmolol can be used asagents for controlled hypotension and are effective in providing ideal surgical field during FESS. Butdexmedetomidine offers the advantage of inherent analgesic, sedative and anesthetic sparing effect.JBSA 2018; 31(2): 67-74